Probing the Relation Between Charge Transport and Supramolecular Organization Down to Ångström Resolution in a Benzothiadiazole‐Cyclopentadithiophene Copolymer. (19th June 2012) - Niedzialek, Dorota; Lemaur, Vincent; Dudenko, Dmytro; Shu, Jie; Hansen, Michael Ryan; Andreasen, Jens Wenzel; Pisula, Wojciech; Müllen, Klaus; Cornil, Jérôme; Beljonne, David
<x xml:space="preserve">Abstract</x> Molecular modeling shows that longitudinal displacement of the backbones by a couple of ångströms has a profound impact on the electronic coupling mediating charge transport in a conjugated copolymer. These changes can be probed by monitoring the calculated X‐ray scattering patterns and NMR chemical shifts as a function of sliding of the polymer chains and comparing them to experiment. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>